OPERA tau neutrino charged current interactions - N. Agafonova (Nature Portfolio, 2021)
Measurement(s) tau neutrino Technology Type(s) detector Sample Characteristic - Environment neutrino beam Sample Characteristic - Location Laboratori Nazionali del Gran Sasso Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14979858